A prática da fé na saúde mental de mulheres muçulmanas em Itabaianinha-SE - Amaral, Grecy Batista (2023)
This research studied the relationship between the practice of faith and the mental health of Muslim women in the town of Itabaianinha. Works on this group at the national level are scarce and, before in Sergipe, they did not exist, giving it an unprecedented character. Through this research, it was intend to listen to the voices of these women. And since this theme involves an interweaving with the religious phenomenon, through practices of faith and religiosity, it was observed the importance of the dialogue between the sciences of religion and the psychology of religion as a way of understanding the human universe, from the belief in your physical, mental, and spiritual well-being. Its general objective was to analyze how the relationship between the practice of faith can act on the mental health of Muslim women in Itabaianinha. As for the specific objectives they were to know the Islamic religion and its interface with the mental health of Muslim women; to know and understand the self-perception that these women have in relation to their practice of faith in their mental health; Knowing the performance of Islam in Itabaianinha and finally, check if there are reports of Islamophobia against Muslim women in that city. So, this research had a qualitative approach with a descriptive and exploratory character, as a methodological strategy. Observations and semi-structured interviews were carried out with Muslim women in the Municipality of Itabaianinha-SE, as it is the location with the highest prevalence of Muslim men and women in the State of Sergipe, due to the existence of two Islamic Centers, a Mosque and an Islamic Association. And for data processing Bardin's content analysis was used. Results relevant to the elucidation of the general and specific objectives were identified, through the collaboration of the interviewees.